2023
DOI: 10.1128/mra.00235-23
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Avian Metapneumovirus Subtype B Vaccine Strains from Brazil

Abstract: Avian metapneumovirus (aMPV) causes a highly contagious upper respiratory and reproductive disease in chickens, turkeys, and ducks. Here, complete genome sequences of aMPV-B vaccine strains BR/1890/E1/19 (PL21, Nemovac; Boehringer Ingelheim Animal Health, Brazil) and BR/1891/E2/19 (1062; Hipraviar, France) were sequenced and compared with the pathogenic field strain VCO3/60616.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This finding was initially not anticipated, considering that only aMPV subtype C has previously been reported in the US turkey population [ 14 ]. Detection and characterization of emerging pathogens such as aMPVs can be performed rapidly using advanced NGS technologies, which can identify divergent strains that are not detected by conventional PCR and enable immediate outbreak response [ 8 , 18 , 19 , 37 ]. As a result of the early detection and confirmation of aMPV subtype B in this study, molecular and serological testing was implemented very quickly for further testing of new samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding was initially not anticipated, considering that only aMPV subtype C has previously been reported in the US turkey population [ 14 ]. Detection and characterization of emerging pathogens such as aMPVs can be performed rapidly using advanced NGS technologies, which can identify divergent strains that are not detected by conventional PCR and enable immediate outbreak response [ 8 , 18 , 19 , 37 ]. As a result of the early detection and confirmation of aMPV subtype B in this study, molecular and serological testing was implemented very quickly for further testing of new samples.…”
Section: Discussionmentioning
confidence: 99%
“…The L and P are non-structural proteins involved in genome replication, while the others code for nucleocapsid, matrix, and envelope structural proteins. The viral envelope is embedded with F (which promotes viral-to-cell membrane fusion), G (a major antigenic determinant involved in viral attachment), and SH (a viroporin involved in membrane permeability) proteins [ 6 , 7 , 8 ]. Proteins N, P, and L encapsulate the viral RNA to form the viral ribonucleoprotein complex (RNP), while the accessory proteins M2-2 and M2-1 are involved in viral genome replication and the 3′-leader/5′-trailer contains viral transcriptional promoters [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the study demonstrated that FTA cards could be used on field-collected clinical samples to obtain high-quality genetic information from RNAs for the untargeted discovery of avian viral agents. In [ 25 ], the Karithii team reported the detection and genome sequence analysis of avian metapneumoviruses circulating in commercial chicken flocks in Mexico by utilizing the approach of direct random sequencing of clinical samples [ 25 , 54 ]. The identification of 11 complete and 2 nearly complete genome sequences of aMPV-A from Mexico was reported.…”
Section: Short-read Sequencing On Poultry and Avian Speciesmentioning
confidence: 99%